Artificial grammar learning: preference for acoustic or visual modality? - Bernardo, Ana Isabel Santos (2015)
This thesis transmits the artificial grammar learning paradigm as an acquisition and processing model of language, within implicit learning investigation. The number of investigations about language and it’s acquisition has increased throughout the years, specifically in the implicit learning ability and artificial grammar learning as the most adequate model to verify it. Language, and namely human language, is an important part in the social universe and requires that each single individual own a cognitive capacity to understand and produce the signs that characterizes and enable verbal communication between humans (Jackendoff, 2002). From Tulving’s 1970 theory until the present, language comprehension and perception has change, but through out times language definition contemplated the memory systems (Gazzaniga et al., 2009). Several authors stated that implicit memory and implicit learning plays a vast role in language acquisition. The present study explores artificial grammar learning paradigm as a model (based on Reber’s study on 1967) to implicit learning and to observe modalities performances differences between and within subjects. Twenty-‐eight subjects participated voluntarily in the present experiment. The study was developed in three consecutive days and in the last task in the last day subjects were informed and expose to sequences with underling grammar. The results reveled significant effects in grammaticality and ACS, an interaction between test days*grammaticality*ACS, specifically significant effects in AGL2 and AGL3, and suggest implicit learning of artificial grammar. These results could be more consistent if the experiment were extended to more days of exposure. The results point out to a tendency in visual modality to demonstrated significant effects, particularly consonants sequences, and imply the visual modality to be the modality with higher tendency to be efficient in artificial grammar learning, namely within the language domain.